2021
DOI: 10.1158/2159-8290.cd-21-0506
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Retroelements and the Viral Mimicry Response in Cancer Therapy and Cellular Homeostasis

Abstract: Features of the cancer epigenome distinguish cancers from their respective cell of origin and establish therapeutic vulnerabilities that can be exploited through pharmacologic inhibition of DNA- or histone-modifying enzymes. Epigenetic therapies converge with cancer immunotherapies through “viral mimicry,” a cellular state of active antiviral response triggered by endogenous nucleic acids often derived from aberrantly transcribed endogenous retrotransposons. This review describes the initial characterization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
91
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 146 publications
7
91
0
4
Order By: Relevance
“…Due to the potential in generating genomic instability, EREs are tightly controlled by epigenetic mechanisms (185)(186)(187). Regarding ERVs, it has been shown that young sequences (i.e., those that have been incorporated into the genome more recently in the evolutionary history and predominantly contain more conserved ORFs) are repressed mainly by methylation of CpG islands in their LTRs and could have their expression reactivated by DNA hypomethylating agents (DHA) such as 5-aza-2′deoxycytidine, while older ERVs are less enriched in CpG islands and are mainly controlled by histone modifications, particularly histone H3 lysine 9 trimethylation (H3K9me3) (188).…”
Section: Endogenous Retroviral Elements and Tumor Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the potential in generating genomic instability, EREs are tightly controlled by epigenetic mechanisms (185)(186)(187). Regarding ERVs, it has been shown that young sequences (i.e., those that have been incorporated into the genome more recently in the evolutionary history and predominantly contain more conserved ORFs) are repressed mainly by methylation of CpG islands in their LTRs and could have their expression reactivated by DNA hypomethylating agents (DHA) such as 5-aza-2′deoxycytidine, while older ERVs are less enriched in CpG islands and are mainly controlled by histone modifications, particularly histone H3 lysine 9 trimethylation (H3K9me3) (188).…”
Section: Endogenous Retroviral Elements and Tumor Immunitymentioning
confidence: 99%
“…Strikingly, treatment of tumor cells with DHA and histone deacetylase inhibitors (HDACi) led to the expression of EREs that could be detected through MDA-5 in the form of cytoplasmic dsRNA, formed by hybridization between complementary RNA strands expressed from bidirectional transcription of EREs (190), homologous EREs transcribed from different loci and from loop structures formed by transcription of DNA stretches containing homologous antisense-oriented EREs sequences (187). This ERE detection by cytoplasmic sensors induces an IFN-mediated antiviral state marked by enhanced cancer cell apoptosis and activation of innate and adaptive immunity that could favor responses to ICB with anti-CTLA-4 (191)(192)(193).…”
Section: Endogenous Retroviral Elements and Tumor Immunitymentioning
confidence: 99%
“…Recent improvements in sequencing technologies and bioinformatic analyses have enabled a rapidly emerging understanding of genome repeat biology ( Mantere et al, 2019 ; O'Neill et al, 2020 ). Activation of transposable elements (TEs) can result in genomic alterations (mutations and chromosomal re-arrangements), modifications to the three-dimensional organization of the genome, transcriptional changes, and generation of nucleic acid species (NAS) that may be detected by innate immune sensing machinery ( Chen et al, 2021 ; Klein and O'Neill 2018 ). Despite the potential physiological benefits of TE integration and propagation throughout the genome, the consequences of TE activation can also be detrimental; therefore, many “counter-balancing” mechanisms have co-evolved with TE integration to keep these potential negative effects in check.…”
Section: Introductionmentioning
confidence: 99%
“…Tri-methylation of histone H3 at lysine 9 (H3K9me3) and DNA methylation (DNAme) occur at the majority of REs and together these epigenetic marks promote transcriptional repression 2 . Recent studies have shown that removal of these marks causes some REs to become active 3 , but the majority of loci remain silent, and molecular features distinguishing expressed REs remain undetermined.…”
Section: Introductionmentioning
confidence: 99%